2012
DOI: 10.4103/0255-0857.93034
|View full text |Cite
|
Sign up to set email alerts
|

Utility of GenoType MTBDRplus assay in rapid diagnosis of multidrug resistant tuberculosis at a tertiary care centre in India

Abstract: MTBDRplus assay had good sensitivity and specificity with turn around time of less than 48 hours. It may be a useful tool for rapid detection of multidrug resistant tuberculosis at a tertiary care centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
14
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
7
14
2
Order By: Relevance
“…Frequencies of katG gene, inhA gene and combined katG and inhA gene mutations in the present study [72/87 (83%), 10/87 (11%) and 5/87 (6%) respectively] are within the range of previously reported studies [13], [22], [23], [24]. Finding of frequency of combined mutations of KatG and InhA in the present study is comparable to a recent study from Mumbai [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Frequencies of katG gene, inhA gene and combined katG and inhA gene mutations in the present study [72/87 (83%), 10/87 (11%) and 5/87 (6%) respectively] are within the range of previously reported studies [13], [22], [23], [24]. Finding of frequency of combined mutations of KatG and InhA in the present study is comparable to a recent study from Mumbai [25].…”
Section: Discussionsupporting
confidence: 90%
“…However, a slightly higher sensitivity (92%) for detection of isoniazid resistance was observed in our study indicating that most of the mutations conferring INH resistance were found in the gene region that were incorporated in the present LPA strip [13]. Sensitivity (97%) and specificity (100%) for detection of MDR-TB in the present study corroborated with a previously reported study [14] and these findings suggest that performance of LPA is similar to conventional DST in a quality-assured TB laboratory.…”
Section: Discussioncontrasting
confidence: 61%
“…[ 10 ] However, results of our study are in good agreement with previously reported studies in MTB pulmonary isolates. [ 9 11 12 ] Thus, the assay demonstrated good concordance with the automated liquid culture-based system for detection of drug resistance in MTB culture isolates from TBM patients. A sensitivity of 93% for INH in this study suggested that most of the mutations conferring INH resistance in MTB CNS isolates are also present in the gene region incorporated in LPA.…”
Section: Discussionmentioning
confidence: 84%
“…The user friendliness and ease of performance of this test within one working day is well documented in many studies and we also had the same experience. [ 9 ] Using BACTEC MGIT DST as a gold standard, the sensitivity and specificity of LPA for INH resistance was 93%, 97% and for RIF resistance 80%, 98.8%, respectively. In comparison, evaluation of this assay from China in MTB isolates of TBM patients has demonstrated 100% concordance in MGIT DST and LPA results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation